Comparison of risk prediction models in infarct-related cardiogenic shock. (14th October 2021) - Freund, A; Poess, J; De Waha-Thiele, S; Meyer-Saraei, R; Fuernau, G; Zeymer, U; Feistritzer, H J; Rubini, M; Oldroyd, K; Windecker, S; Montalescot, G; Schneider, S; et al.
Abstract: Background: Several prediction models have been developed to allow accurate risk assessment and provide better treatment guidance in patients with infarct-related cardiogenic shock (CS). However, comparative data between these models are still scarce. Objectives: To externally validate different risk prediction models in infarct-related CS and compare their predictive value in the early clinical course. Methods: The Simplified Acute Physiology Score (SAPS)-II Score, the CardShock score, the IABP-SHOCK II score and the Society for Cardiovascular Angiography and Intervention (SCAI) classification were each externally validated in a total of 1055 patients with infarct-related CS enrolled into the randomized CULPRIT-SHOCK trial or the corresponding registry. Discriminative power was assessed by comparing area under the curves (AUC) in case of continuous scores. Results: In direct comparison of the continuous scores in a total of 161 patients, the IABP-SHOCK II score revealed best discrimination (AUC=0.74), followed by the CardShock score (AUC=0.69) and the SAPS-II score, giving only moderate discrimination (AUC=0.63). All of the three scores revealed acceptable calibration by Hosmer-Lemeshow test. The SCAI classification as a categorical predictive model displayed good prognostic assessment for the highest risk group (stage E), but showed poor discrimination between stages C and D with respect to short-term-mortality. Conclusion: Based on the present findings, the IABP-SHOCK II score appears to be the most suitable of the examined models for immediate risk prediction in infarct-related CS. Prospective evaluation of the models, further modification or even development of new scores might be necessary to reach higher levels of discrimination. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): European Union, German Centre for Cardiovascular Research